Ficha Resumen: Etapa de Planeación. - Víquez-Paniagua, Ana Gabriela (My University, 2017)
El objeto comprende aspectos relevantes de la etapa de planeación tales como su proposito, razones para planear y los contenidos de un buen plan.

The object contains the relevant aspects of the planning of the project, such as their porpuse, the reasons for planning and the contents that a good plan must have.
Keywords: Administración de proyectos; Planeación; Objetivos; Administración de los recursos; Costos; Precios; Riesgos; Project management; Planning; Resource Management; Costs; Prices